2021
DOI: 10.3390/ijns7040065
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Course of Hypothyroidism Detected through Neonatal TSH Screening in a Population-Based Cohort of Very Preterm Infants Born at Less than 32 Weeks of Gestation

Abstract: After several decades of successful newborn screening (NBS) for congenital hypothyroidism, the optimal hypothyroidism NBS algorithm for very preterm infants is still controversial. Due to concerns about an elevated risk of a false-negative initial thyroid-stimulation hormone (TSH) screening, repeat NBS has been implemented for this group. While transient hypothyroidism is known to be more frequent among very preterm infants, the prevalence of permanent hypothyroidism is generally assumed to be the same as in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Although the number of reports of transient hypothyroxinemia in premature infants and considerations regarding the principles and indications for initiating LT4 treatment is increasing, universal rules have not yet been established. Some recommendations propose that the assessment should be limited to TSH and FT4 in children born before the 32 nd week of gestation and with a birth body weight (BBW) lower than 1500 g, also in critically ill children or children from twin pregnancies ( 3 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of reports of transient hypothyroxinemia in premature infants and considerations regarding the principles and indications for initiating LT4 treatment is increasing, universal rules have not yet been established. Some recommendations propose that the assessment should be limited to TSH and FT4 in children born before the 32 nd week of gestation and with a birth body weight (BBW) lower than 1500 g, also in critically ill children or children from twin pregnancies ( 3 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immature hypothalamo-pituitary-thyroid axis and thyroid dysfunction are frequently encountered in newborn babies and especially in premature babies (11). Although the relationship between CH and its morbidities in premature babies has been evaluated, the effect of CH on morbidity is still unknown [6][7][8][9][10] . It is known that newborn babies with SGA are at risk for endocrine problems in their advanced ages 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate levothyroxine dose was determined by measuring serum fT4 and TSH levels at regular intervals (once a week). Based on our routine protocol, all patients admitted to the NICU were diagnosed and treated according to this guideline [10][11][12]21 . The patients who were followed by two Neonatologist (DY, CT) were included in this study.…”
Section: Examination Of Thyroid Function Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating large CH cohorts demonstrate enrichment of preterm cases ( 4 , 16 , 34 ). However, the data are conflicted in defining whether prematurity is associated with permanent ( 17 ) or transient dysfunction ( 35 , 36 ) or both ( 37 ), and the extent to which preterm birth can be used as a reliable predictor of TCH is not clear. Barry et al ( 15 ) confirmed a significant association but others have generally failed to implicate gestational age in this role ( 22 , 24 , 38 ).…”
Section: Preterm Infant and Thyroid Dysfunctionmentioning
confidence: 99%